2015
DOI: 10.1007/s00421-015-3127-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in metabolic and inflammatory responses in lower and upper body high-intensity intermittent exercise

Abstract: In conclusion, our results demonstrated that despite the higher performance in lower body HIIE, the inflammatory response did not differ between exercise modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…When the rate of glucose metabolism exceeds the oxidative capacity of the mitochondria (Dienel, 2013), lactate assists as a critical buffer, allowing glycolysis to rapidly produce significant amounts of energy. The higher variation in glucose after the HIIE1.25 compared to the HIIE2.5 may indicate that shorter HIIE stimulated glyconeogenesis (through an increase in catecholamines); however, as the exercise was very short, this glucose was probably not used during the exercise (Lira et al, 2015). On the other hand, the clearance of lactate during the recovery period was not measured, limiting a comparison between lactate levels after both HIIEs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the rate of glucose metabolism exceeds the oxidative capacity of the mitochondria (Dienel, 2013), lactate assists as a critical buffer, allowing glycolysis to rapidly produce significant amounts of energy. The higher variation in glucose after the HIIE1.25 compared to the HIIE2.5 may indicate that shorter HIIE stimulated glyconeogenesis (through an increase in catecholamines); however, as the exercise was very short, this glucose was probably not used during the exercise (Lira et al, 2015). On the other hand, the clearance of lactate during the recovery period was not measured, limiting a comparison between lactate levels after both HIIEs.…”
Section: Discussionmentioning
confidence: 99%
“…Lira et al (2015) submitted athletes to 4 sessions of the Wingate test at 100% of VO 2peak and observed an increase in IL-10 levels, inducing beneficial alterations in the resting inflammatory profile. Dorneles et al (2016) demonstrated that 10 × 60 s at 85–90% of maximal aerobic power, separated by 75-s at 50% of maximal aerobic power (which gives a mean workload of 65.6–67.8% of P max ), was able to induce a progressive elevation of IL-6 and IL-10 levels immediately and 30-min post exercise in both lean and overweight-obese subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to health benefits, intense exercise increases interleukin 6 (IL6) concentration by increasing its production in skeletal muscles, active in the regulation of energy supply in the muscles [18,27]. Moreover, higher expression of IL6 results in increased expression of the anti-inflammatory cytokine IL10.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that basketball Paralympic athletes and athletes competing in Judo and Wrestling, for example, normally execute repeated high-intensity actions during their competitive disputes. The understanding of the energy system dynamics during high-intensity interval exercise is important to improve the comprehension of the stimulus generated and, consequently, of the probable long-term adaptation to such effort (Lira et al, 2015). Thus, the main objective of this study was to investigate the performance and energy systems contribution during four upper-body Wingate tests interspersed by 3-min intervals.…”
Section: Introductionmentioning
confidence: 99%